(Dis)satisfaction of health professionals who work with oncology - Maiara Bordignon; Lucimare Ferraz; Carmem Lúcia Colomé Beck; Simone Coelho Amestoy; Letícia de Lima Trindade (Universidade Federal do Ceará, 2015)
Objective: identify sources of satisfaction and dissatisfaction at work for health professionals who work with oncology. Methods: Qualitative research conducted with 31 professionals from a multidisciplinary health team who worked in an Oncology Inpatient Unit of a public hospital in the south of Brazil, using a semi-structured interview, analyzed according to Bardin's proposal. Results: the main sources of job satisfaction emerged from the relationship between patients and health professionals. The dissatisfaction sources were connected to the working environment and conditions. Conclusion:. A humanized look to health professionals who work with oncology, with changes in their work environment seems to be relevant in the context investigated.